Keabsahan Haji Dengan Talangan Perspektif Para Ulama - Isnaini, Chairul Fajar; Hayatuddin, Ah. Kholis (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2024)
Hajj Bailout Financing is a loan from a sharia bank to a customer to cover the lack of funds to obtain a Hajj seat at the time of repayment of BPIH (Hajj Travel Costs). It is known that the Hajj bailout fund agreement at a sharia bank contains multiple contracts, where the contract used is Qard wal Ijarah. From the perspective of muamalah fiqh, qardh and ijarah are permissible. Meanwhile, several studies state that in the view of Islamic law regarding taking ujrah fees from the hajj bailout funds is not in accordance with sharia because the percentage of ujrah fees obtained is based on the amount of funds from qardh. Interestingly, researchers will analyze whether or not carrying out the Hajj is valid using bailouts, while one of the conditions for carrying out the Hajj is istita'ah. This research uses descriptive analysis techniques. What is meant by descriptive analysis is an assessment by explaining data that has been collected and arranged well. According to most scholars, the basic law of bailouts is that it is permissible, including for religious purposes. However, it is necessary to pay attention to the legal requirements for the use of bailout funds. If the use of these funds is self-imposed, this is not permitted and other variables must be looked at. For example, does the person receiving the bailout potentially have the ability to pay it or not at the time of the bailout agreement? If it turns out he doesn't have the ability or is forcing himself, then that is not permitted.